Sovereignty and Obedience: violence in Hobbes and Harrington - Caram, Cintia (ARFIL y UNL, 2022)
Sovereignty and obedience were two key notions in the discussions that took place at the dawn of modernity. Part of the debates focused on the question of the legitimacy of political power and, consequently, why we should obey, what benefits obedience brings and what are its limits. In all these cases, the notion of violence appears with different faces, and mainly with the physiognomy of war —point of maximum expression of explicit violence—, a problem that the political authority comes, in some way, to solve. The sovereign State, however, far from being the representation of Irenism, becomes a legitimate monopoly of violence. This work aims to address such issues from the theories of Hobbes and Harrington. Both justified the obligation of the subjects to abide by the law that is imposed and that guarantees, above all things, their lives.